First record of the genus Darnilia van Achterberg, 1989 (Hymenoptera: Braconidae: Rogadinae) from Vietnam, with description of three new species - Long, Khuat Dang; Achterberg, Cornelis Van (Zootaxa, 2018)
Three new species of the genus Darnilia van Achterberg, 1989 from Vietnam, viz. D. granulata Long & van Achterberg, sp. n., D. intermedia Long & van Achterberg, sp. n. and D. vietnamica Long & van Achterberg, sp. n., are described and illustrated. This is the first record of the genus Darnilia for Vietnam. A key to the species of the genus Darnilia is provided.